Impact of Technology-enhanced Pedagogy towards Students’ Academic Attitudes in the National Language in Uganda: A Quasi-Experimental Study in the Secondary Schools in Mbarara City - Arishaba, Ms. Emilly; Balimuttajjo, Dr. Sudi; Muwonge, Dr, Charles (American Journal of Education and Practice, 2025)
Purpose: This study assessed the impact of technology-enhanced pedagogy on students' academic attitudes towards Kiswahili language learning in secondary schools in Mbarara City, Uganda. Materials and Methods: Employing a quasi-experimental design, the study compared two groups: an experimental group (N = 79) taught using technology-enhanced methods (e.g., audio, video, and interactive media) and a control group (N = 79) taught using traditional methods such as lectures and textbooks. Stratified random sampling was utilized to select a total of 158 participants. The main data collection instrument was the Foreign Language Learning scale, supplemented with additional bio-data. A pre-post test was conducted over three months, and data were analyzed using descriptive statistics and paired-samples t-tests in Statistical Package for Social Sciences version 26. Findings: The results revealed that the experimental group showed a significant improvement in academic attitudes, with a post-intervention mean of 3.7 (SD = 7.0) compared to the pre-intervention mean of 1.0 (SD = 5.9), t(78) = 2.5, p = 0.013. In contrast, the control group showed no significant change, with a post-intervention mean of 0.8 (SD = 4.3) compared to the pre-intervention mean of -0.7 (SD = 5.8), t(78) = 1.7, p = 0.095. Implications to Theory, Practice and Policy: These findings suggest that technology-enhanced pedagogy has a significant positive impact on students' academic attitudes, while traditional methods did not yield similar improvements. The study highlights the potential of integrating technology into language education and emphasizes the need for further research on the long-term effects of technology in diverse educational contexts.